PP.01.06: INCIDENCE OF HYPERTENSION IN MEN AND WOMEN WITH CORONARY CHRONIC TOTAL OCCLUSION. (June 2015) - Bryniarski, L.; Surowiec, S.; Klima, L.; Terlecki, M.; Jankowski, P.; Rajzer, M.; Kusak, P.; Krolikowski, T.; Curylo, A.; Zmudka, K.; Dudek, D.; Czarnecka, D.
Abstract : Objective: Hypertension is the one of the most common risk factor of coronary heart disease (CAD). Less is known about rate of hypertension in patients with chronic total occlusion (CTO). This study compared rate of hypertension in men and women treated by percuteaneous coronary intervention of CTO. Figure. No caption available. Design and method: 150 patients underwent 159 procedures for percutaneous revascularization of CTO of 153 vessels. Of the 159 procedures, 124 (78%) were performed using an antegrade approach and 34 (22%) using a retrograde approach. Incidence of risk factors and succes rate of procedures between men and women were compared. Results: In the study groups 122 patients were men (81.3%). The average age of men and women were 60.9 ± 9.7 years and 67.1 ± 7.5 years, respectively (p = 0.002). The incidence of hypertension and other risk factors were presented in Table. The succes rate was similar in both groups 88.3% vs 82.1% (p = NS). No serious complication were observed. Conclusions: Although higher age of women, main risk factors were similar in both groups and hypertension remains, next to the hypercholesterolemia, the most frequent risk factors of coronary artery disease in patient with chronic total coronary occlusion. We have to emphasized that the incidence of hypertension and hypercholesterolemia in patients with CTO is higher than other CAD patients.